Analisis Efektivitas Mesin Hot Press Yamamoto 45 Opening Menggunakan Metode Overall Equipment Effectiveness dan Fault Tree Analysis: Analysis of the Effectiveness of the Yamamoto 45-Opening Hot Press Machine Using Overall Equipment Effectiveness and Fault Tree Analysis Methods - Rawan S, Hend; Raliby Al Manan, Oesman; Rosyidi, Muhammad Imron (Universitas Muhammadiyah Magelang, 2026)
T This thesis entitled